The role of psychological capital in enhancing job integration: An analytical study of the opinions of a sample of employees in four- and five-star hotels in the city of Sulaymaniyah/Kurdistan Region - Iraq - Walaa Jawdat Ali Al-Jaf,; Dalia Khaled Faeq, (The Scientific Journal of Cihan University– Sulaimaniya, 2019)
The purpose of the current study is to analyse the role of Psychological capital and its dimensions (self-efficacy, optimism, hope , resiliency) on employee work engagement ( vigor, dedication, and absorption) in four and five star hotels in the city of Sulaymaneyah in the Kurdistan Region of Iraq. In order to achieve the objectives the questionnaire was used as a basic tool for collecting data and information. (300) questionnaires were distributed to employees in the surveyed hotels, 283 were returned, 275 of which were valid for analysis. The most prominent being the existence of a positive correlation and a significant effect of the independent variable (psychological capital) in the dependent variable (work engagement ). Based on the conclusions, the study reached a number of recommendations. Most important of which is the need for hotels to adopt the concept of psychological capital in thought and practice and to include it in the curriculum of the training courses for senior leaders so that many of them can identify the philosophy of applied and requires the management of hotels investigated increase the level of attention to positive internal ethical standards and values Towards the achievement of functional integration and taking all the ways to prevent its achievement and work on its development and make it the cornerstone, which can contribute to a positive change in performance.